Farmer-led innovations: Best practices and lessons learnt in livestock rearing - KUMAR, RAKESH; SINGH, PREMLATA; NIKAM, VINAYAK R; SHARMA, J P (The Indian Journal of Animal Sciences, 2016)
The livestock sector contributes 4.11% in overall GDP, however, its full potential has not been utilized, necessitating need of innovations and the use of best practices for sustainable and profitable production. Farmers are a rich source of indigenous knowledge and they innovate, experiment and adapt continuously. Documentation of these success stories may serve as a lightening conductor for other farmers. The study was carried out with 35 progressive farmers from 10 agro-climatic regions of Karnataka. The study found that stall feeding for sheep, silage preparation and storage in bunkers, low cost dairy shed and locally made milking machine were innovations made by farmers. New technology adopted by the farmers included improved crossbreeds of sheep, emu farming, high tech dairy unit and fast growing breeds of pig. Farmers frequently used literature and KVK personnel as a source of information. Development of marketing linkages, direct marketing and contract farming were important aspects in post production operations. Farmers used some of the best practices like integrated farming system; clean and hygienic methods of milking, regular vaccinations, daily chart of feed, silage and bunker storage, rotation period, use of high jet water spray for washing of animal etc. Study concluded that qualities and traits like ability to select and integrate enterprise wisely; knowing and judging market demand correctly; developing market linkages; constant seeking of information and practical intelligence to use locally available resources were the key to success of dairy farmers. Dairy extension should play a pivotal role in imparting training to farmers about these aspects and spreading the success of these innovative farmers through literature in other parts of the country for its replication on large scale.